2016
DOI: 10.1007/978-3-319-33951-1_4
|View full text |Cite
|
Sign up to set email alerts
|

A Formal Security Analysis of ERTMS Train to Trackside Protocols

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…A high-level security analysis of ERTMS is made in [13] but does not present the vulnerabilities of the EuroRadio protocol that will be exploited with this framework. Different vulnerabilities of the EuroRadio protocol are pointed out in [3] by performing an analysis of it with the ProVerif tool. These vulnerabilities include, for instance, the ability of including high-priority messages or deletion of messages, since the session establishment process does not use timestamps and, therefore, these messages could be replicated.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…A high-level security analysis of ERTMS is made in [13] but does not present the vulnerabilities of the EuroRadio protocol that will be exploited with this framework. Different vulnerabilities of the EuroRadio protocol are pointed out in [3] by performing an analysis of it with the ProVerif tool. These vulnerabilities include, for instance, the ability of including high-priority messages or deletion of messages, since the session establishment process does not use timestamps and, therefore, these messages could be replicated.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, the EuroRadio protocol is used to ensure the authenticity and the integrity of the communications. However, it has been proved that both protocols have vulnerabilities [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…After authentication, the trackside equipment will synchronise its clock upon receipt of the first message from the train. The EuroRadio and Application Layer protocols have previously been formally analysed [6], where it was shown that while both layers prevent an attacker from learning the secret key, there are flaws in the protocol, for instance allowing unauthenticated 'Unconditional Emergency Stop' messages being sent by an attacker. There is no existing work to our knowledge, however, which attempts to fuzz the EuroRadio or Application Layer protocols at this time.…”
Section: Application Layer Protocolmentioning
confidence: 99%
“…We continue by computing the value of the last message block m f l+2 , such that m f has the same MAC as the original message, using Eq. (6) and H…”
Section: Forging Train Control Messagesmentioning
confidence: 99%
See 1 more Smart Citation